Open FOAM simulations of the supersonic flow around cones at angles of attack - Lorenzon, Denis (2019)
The supersonic flow around conical bodies is a very important issue in aerospace engineering, with many applications in internal and external supersonic aerodynamics. Non-viscous supersonic flow about yawing cones is essentially 3-dimensional, but it shows some characteristics regarding the conical flow around circular cones with zero angle of attack. In this latter case, the complete flow structure is axisymmetric and can be described by an ordinary differential equation known as the Taylor-Maccoll equation.